Everyday Observations: Developing a Sociological Perspective through a Portfolio Term Project - Johnson, David; Renzulli, Linda; Bunch, Jackson (TRAILS: Teaching Resources and Innovations Library for Sociology, 2013)
We describe a semester-long active learning project in which students practice the skills of synthesis and analysis by developing portfolios organized around a topic of their own choosing (relevant to their substantive course). We build on prior contributions in four ways. First, we offer a project that is indicative of basic skills in the sociological toolkit and therefore of potential relevance to students’ lives and future careers. Second, we provide the first systematic assessment of the efficacy of course portfolios by using a controlled, pretest-posttest analysis conducted in seven sections of three separate sociology courses. Third, we illustrate the conceptual connections between active learning pedagogy and identity theory and provide evidence that portfolios influence the development of a sociological identity and thought among students. Fourth, we offer instructors an instructional tool that can be employed in any undergraduate sociology course.